Corporate Social Responsibility, an Analysis of Labor Practices Applied in the Province of Imbabura-Ecuador - Arias, Wilmer Medardo (2020)
The employment situation in the business sectors must be analyzed with social responsibility and assumed with the voluntary commitment of the companies, which allows to ensure economic, social and environmentally responsible growth for which it is necessary to analyze the situation of the socially responsible practices of the entrepreneurs with respect to their economic activities, whose study is framed within the qualitative and quantitative modality, applying theoretical level methods, for the diagnosis to several companies in the province of Imbabura-Ecuador, applying the survey technique, as results Important was the perception of employers, determining that there is not enough commitment regarding fair labor practices.